Pengaruh Penambahan Core Stability Exercise Pada Muscle Energy Technique Terhadap Penurunan Nyeri Myofacial Trigger Point Upper Trapezius Pada Pembatik PT Danar Hadi - Lubis, Dedy Kurniawan; , Totok Budi Santoso, S.Fis., MPH; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc (2015)
Background: Myofascial Trigger Point Syndrome (MTPS) is one of the conditions causing pain originated from nerves, bones and joints. MTPS itself is a syndrome arises due to the affectivity of one or more trigger points in the muscle fibers. Provision of therapeutic modalities for myofacial trigger points in the upper trapezius is muscle energy technique combined with core stability exercise and single application of muscle energy technique. Objective: This study aimed to determine the effectiveness of the administration of muscle energy technique combined with core stability exercise and single application of muscle energy technique. Methods: Quasi eksprimental with two grop pre and pst test design. The population in this study is written in PT Batik batik Dana Hadi, the total respondents 30 people, with details of the first group 15 and the second group of 15 people. Measurements carried out with VAS pain score, the results were analyzed using Paired Sample T-test and test independent sample t-test. Result: Paired Sample T-test in both groups showed p = 0.000 <0.05, which means there is the influence of muscle energy technique therapy with the addition of core stability exercise and only using muscle energy technique to decrease pain myofacial upper trapezius trigger point. Based on the average value group of muscle energy technique with the addition of core stability have an average exercise greater influence than just using muscle energy technique (7.4800> 5.7933) test results Independet Sample T-test on clogs I shows the results of p > 0.05 (63.390> 2.145 and 0.000> 0.05) and in group II, p> 0.05 (59.226> 2.048 and 0.000 <0.05), which means there is a significant difference between the two groups .. conclusion: the use of muscle energy technique with the addition of core stability exercise is better than just using muscle enegy myiofacial technique in reducing pain upper trapezius trigger point. Keywords: muscle energy technique, core stability exercise, myofacial upper trapezius trigger point.